2021
DOI: 10.3389/fpsyg.2021.635300
|View full text |Cite
|
Sign up to set email alerts
|

Humor of the Leader: A Source of Creativity of Employees Through Psychological Empowerment or Unethical Behavior Through Perceived Power? The Role of Self-Deprecating Behavior

Abstract: Although we use humor in our daily communication, there still needs to cognize its effects on the attitudes and behavior of the employees. Based on benign violation theory (BVT), the study proposes that leader's humor (LH) conveys social information about counter norms. The BVT has been amalgamated with social information processing theory (SIPT) to develop hypotheses assuming the consequences of LH on the attitude and behavior of the employees. This study hypothesizes that even though LH is linked positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 110 publications
0
15
0
Order By: Relevance
“…48,50 SIP model believes that social environment contains important information clues, and employees will shape their own attitudes and behaviors through these information clues. 52 Based on SIP model, both work-related LMX and non-workrelated SSG can be used as important information/resources for employees. 38,40 However, work-related LMX and nonwork-related SSG will affect employees' attitude (AC) in different ways.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…48,50 SIP model believes that social environment contains important information clues, and employees will shape their own attitudes and behaviors through these information clues. 52 Based on SIP model, both work-related LMX and non-workrelated SSG can be used as important information/resources for employees. 38,40 However, work-related LMX and nonwork-related SSG will affect employees' attitude (AC) in different ways.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Many researches have focused on the key mediating role that psychological empowerment plays a role between leadership style and employee attitudes, emotions, and behaviors (Chen et al, 2019;Jing and Zhou, 2019;Rosenberg et al, 2021). Existing research has confirmed that leader humor is a successful empowerment management practice that effectively stimulates employees' perceptions of empowerment, influencing their work attitudes and behaviors (Gkorezis et al, 2011;Ali et al, 2021).…”
Section: Mediating Role Of Psychological Empowermentmentioning
confidence: 99%
“…Thus, as an empowerment management strategy, leader humor can remove the interpersonal obstacles associated with formal hierarchies in the workplace and increase the sense of empowerment of subordinates (Gkorezis et al, 2011;Jia and Liu, 2021). When leaders and employees communicate with humor, this case not only makes the work more meaningful (Duncan, 1982) but also enhances employees' work autonomy, self-efficacy and self-confidence (Jiang et al, 2020;Ali et al, 2021), thereby improving employees' perception of impact on the job. The sense of work meaning, selfefficacy, self-determination, and work impact experienced by subordinates is exactly the four sub-dimensions of psychological empowerment.…”
Section: Mediating Role Of Psychological Empowermentmentioning
confidence: 99%
See 2 more Smart Citations